Productivity growth, catching-up and uncertainty in China’s meat trade - Nin-Pratt, Alejandro; Hertel, Thomas W.; Foster, K.; Rae, A. (Wiley, 2004)
The potential role of China as a major importer of agricultural products, and the likely impact on world markets has been a topic of considerable debate over the past decade. In this paper, we focus specifically on the livestock sector and develop a detailed analysis of productivity growth in China’s pig and poultry production along with projections of China’s likely meat trade in the year 2010. We use a general equilibrium model which permits us to explore the sensitivity of our projections to macro-economic uncertainty as well as uncertainty in livestock productivity growth rates. Our analysis shows that China’s net trade position is very sensitive to both of these factors. With high livestock productivity growth and a slow-down in the rest of the economy, China could be a substantial competitor in export markets by 2010. On the other hand, slow productivity growth in livestock production, coupled with a rapidly growing macro-economy could transform China into a major market for future meat exports.